Photoelectric properties of ZnS/Au/ZnS transparent conductive tri-layer films. (1st September 2017) - Wang, Caifeng; Hu, Bo
Highlights: High quality ZnS/Au/ZnS tri-layer films were prepared by pulsed laser deposition. Effect of annealing temperature on the photoelectric properties of ZnS/Au/ZnS was investigated. A good system annealed at 200 °C with a sheet resistance of 27 Ω/sq and a figure of merit of 3.815 × 10 −3 Ω −1 is obtained. Abstract: ZnS/Au/ZnS tri-layer films are deposited on quartz glass by pulsed laser deposition (PLD) at room temperature, and have been annealed in air at different temperatures. The effect of annealing temperature on the optical and electrical properties of ZnS/Au/ZnS tri-layer films is investigated. X-ray diffraction (XRD) patterns show that the increase in annealing temperature improves the crystallinity of the structures. Scanning electron microscope (SEM) images of the samples show that the particle size becomes larger as the annealing temperature increases. Moreover, with the increase of annealing temperature, sheet resistance of the tri-layer films decreases initially, and increases further by increasing the annealing temperature to 300 °C. High quality ZnS/Au/ZnS tri-layer films with the sheet resistance of 27 Ω/sq and the maximum optical transmittance of 86.2% in the visible light region (400–800 nm) are obtained when the sample is annealed at 200 °C. The figure of merit is calculated to evaluate the performance of ZnS/Au/ZnS tri-layer films.